All Days 2003
DOI: 10.2118/81715-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Well Review of Coiled Tubing Force Matching

Abstract: TX 75083-3836 U.S.A., fax 01-972-952-9435. AbstractTo increase the predictability of successful coiled tubing operations, a review of recorded versus predicted weights was undertaken for several Statoil operated Norwegian platforms. Results from thirty-three wells were analysed and showed that a coefficient of friction of 0.24 was applicable in most wells. Additionally, it was confirmed that deviation complexity, production rates and direction of travel had no effect on the friction coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…As far as the authors are aware, the relationship between temperature and CoF was never investigated for CT operations, either experimentally or theoretically. A similar study was reported by Kaarstad et al (2009) for drilling operations. There are several differences between wet dynamic friction for CT and for drilling operations.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…As far as the authors are aware, the relationship between temperature and CoF was never investigated for CT operations, either experimentally or theoretically. A similar study was reported by Kaarstad et al (2009) for drilling operations. There are several differences between wet dynamic friction for CT and for drilling operations.…”
Section: Introductionsupporting
confidence: 80%
“…However, it was observed that, in general, between 20 and 70 C, CoF decreases as temperature increases to approximately 40 to 45 C and then increases as tem-perature is increased further. Kaarstad et al (2009) obtained similar results (CoF increases with temperature) and proposed that fluid viscosity may be responsible for this effect (fluid viscosity decreases as temperature increases). They proposed a simple linear temperature dependence of CoF,…”
Section: Temperature-dependent Friction Modelmentioning
confidence: 54%
See 1 more Smart Citation
“…Craig (2003) reviewed coiled tubing injector weight data for 33 oil-producing wells and concluded that a constant friction coefficient of 0.24 was representative for most operations. Newman et al (2003) report that residual bending of coil increases the contact forces and effective friction significantly and show that the effective static friction coefficient is s ϭ 0.3 Ϯ 20%.…”
Section: Coefficient Of Frictionmentioning
confidence: 99%
“…Moreover, the friction factor, µ, highly depended on the roughness of contact surfaces, properties of the drilling fluid, and temperature and pressure conditions. Craig [56] analyzed 33 wells in a Norwegian platform and reported that µ = 0.24 was the most applicable friction factor for all types of wells, and the condition of the well trajectory had an insignificant effect on the friction factor. Table 1 lists the friction factors between the drill pipes and wellbore wall using different drilling fluids, as reported by Samuel [57].…”
mentioning
confidence: 99%